Perancangan Karakter Boardgame “Jejak Karapas: Pahlawan Laut Kecil” Dengan Pemanfaatan Enam Jenis Penyu Laut di Indonesia - Nabilla, Zahra Rizky; Rizky, Zahra Rizky; Romadhona, Mahimma; Arifianto, Pungky Febi (UNIVERSITAS STEKOM, 2025)
Sea turtles play an essential role in marine ecosystems but are increasingly threatened by human activities. Promoting conservation awareness from an early age through engaging educational tools is crucial. This study presents the development of an educational board game titled “Jejak Karapas: Little Ocean Heroes”, designed to teach children aged 10–13 about sea turtle conservation in Indonesia. The game’s character designs were informed by scientific research and adapted to suit children's aesthetic preferences. Validation results indicated that expressive and imaginative characters resonated most with players. The game serves as a creative medium to encourage environmental responsibility in a fun and approachable format for young audiences.